Advancing JSEPA’s Social Equity Charge - Michelle D. Evans; Hillary J. Knepper (Journal of Social Equity and Public Administration)
The Journal of Social Equity and Public Administration (JSEPA) reiterates our mission, aims and scope to support original research and discussions aimed at illuminating inequities, advancing justice and reducing disparity within the public service sphere. The co-editors-in-chief briefly discuss the current environment for JSEPA, some new opportunities for scholarship, introduce new members of the JSEPA family, and highlight recently departed and solely missed colleagues.